RNAseq data from 112 samples of benign or malignant ovarian tumours - Uppsala University (Uppsala University, 2025)
This dataset contains ~1.2 TB RNA sequencing data in fastq format from 112 samples of fresh-frozen ovarian tumours from a total of 111 women, two samples being replicates. The samples were collected from the U-CAN collection at Uppsala Biobank and include both benign (n = 18) and malignant (n = 94) tumours.
The RNA sequencing samples were sequenced using paired-end sequencing (2x150 bp) on an Illumina NovaSeq 6000 instrument at the SciLifeLab National Genomics Infrastructure (NGI) in Uppsala.

This dataset is included in the study "Total RNA expression in benign ovarian and malignant ovarian tumours" (http://identifiers.org/ega.study:EGAS50000001045).
Keywords: transcriptomics; cancer; health; human; Genetics and Genomics; Genetik och genomik